2020
DOI: 10.1186/s12879-020-4882-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between climate, geography and respiratory syncitial virus hospitalizations among children in Ontario, Canada: a population-based study

Abstract: Background: Respiratory syncytial virus (RSV) infection is a major cause of hospitalization in young children in Canada, despite routine immunoprophylaxis in those with medical risk factors. We aimed to determine if cold temperatures are associated with RSV hospitalization. Methods: We conducted a population-based nested case-control study of children in Ontario, Canada, using health administrative data. We compared children hospitalized for RSV between September 1, 2011 and August 31, 2012 to age and sex matc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Certainly, there are evident discrepancies in the published data, and some studies did not confirm a relationship between the particular air pollutants and RSV; for example, an analysis of 1670 RSV hospitalizations in children under 36 months of age matched with 6680 controls showed an increased risk of hospitalization in relation to higher annual ozone levels (OR = 1.03 per 1 parts per billion/ppb increase), but not with annual PM 2.5 or NO 2 , yet the authors concluded that these figures might be underestimated due to the annual values that were used for the calculations [ 19 ]. On the other hand, an analysis of 266 infants with RSV bronchiolitis showed lower and higher PM 10 , PM 2.5 , benzene, NO, and SO 2 concentrations in the months with a high RSV activity, although the only independent predictor of the RSV incidence was the benzene concentration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, there are evident discrepancies in the published data, and some studies did not confirm a relationship between the particular air pollutants and RSV; for example, an analysis of 1670 RSV hospitalizations in children under 36 months of age matched with 6680 controls showed an increased risk of hospitalization in relation to higher annual ozone levels (OR = 1.03 per 1 parts per billion/ppb increase), but not with annual PM 2.5 or NO 2 , yet the authors concluded that these figures might be underestimated due to the annual values that were used for the calculations [ 19 ]. On the other hand, an analysis of 266 infants with RSV bronchiolitis showed lower and higher PM 10 , PM 2.5 , benzene, NO, and SO 2 concentrations in the months with a high RSV activity, although the only independent predictor of the RSV incidence was the benzene concentration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In-depth analyses have focused on the attention to particulate matter characterized by an aerodynamic diameter no greater than 10 μm and 2.5 μm (PM 10 and PM 2.5 ), sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), and carbon monoxide (CO). According to the literature, the increased risk for RSV-related hospitalizations or emergency department consultations has been associated with exposure to PM 10 [ 10 , 11 , 12 , 13 , 14 ], PM 2.5 [ 13 , 16 , 17 ], benzene [ 18 ], NO 2 [ 11 , 13 ], ozone [ 19 ], or SO 2 [ 11 ], yet in the latter case, there are also contradictory reports [ 13 ]. Fewer analyses focused on RSV morbidity in an outpatient setting, but a large-scale Chinese study by Qing Ye confirmed a correlation with PM 2.5 , PM 10 , SO 2 , NO 2 , and CO, emphasizing an association with the dosage, length of exposure (lag), or cumulative effects, also suggesting possible cut-off values specific for each pollutant [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…reported a median age of 9 months. [ 13 ] Thomas et al . also observed male predominance (51%) over females (49%).…”
Section: Discussionmentioning
confidence: 99%
“…also reported a male predominance (63.8%) in their study. [ 13 ] RSV infection occurs worldwide, especially during the winter months, and majority children are infected till they reach age of 2 years, but, lower respiratory tract symptoms develop in only 40% of them. [ 17 18 ] Presently also, cases presented in winter months that is from November to March.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple geographic factors may also interact to alter outcomes through complex or poorly defined mechanisms. For example, one study conducted in Ontario, Canada identified colder temperatures, increased ozone levels, and lower income neighborhoods as risk factors for hospitalizations for RSV in children between the ages of 0 and 36 months [79]. Similar data for preterm infants with respiratory disease is lacking.…”
Section: Other Geographic Factorsmentioning
confidence: 99%